Design Analysis and Design of Coolbox Based on Thermoelectricity with Wind Power Plant Using 3D Modeling - Andri Adi Seftandi; Siti Laily Masnah; Muhammad Ihsan; Airlangga Adi Satria; Wahyu Sunanda Abdul Imam; Apri Wiyono (Universitas Negeri Padang, 2022)
Energy needs continue to increase from year to year in line with population growth in Indonesia. Therefore, wind turbines as a renewable alternative energy source to meet the energy needs of coastal communities. The use of heavy and high ice blocks has always been a problem for fishermen in fish catches, this has an impact on the quality of the fish caught. This thermoelectric coolbox with wind power plant is designed by combining the components of a thermoelectric coolbox and a wind turbine which functions to maintain the temperature in the coolbox so that the fish stored are more durable using electricity generated from the rotation of the wind turbine. This research uses the design and development (D&D) method and is supported by secondary data from published articles and news journals which aim to design a three-dimensional model of a thermoelectric coolbox using solidworks software. The results of the design analysis obtained turbine area, turbine height, chord length, torque value, shaft diameter and allowable shear stress. With the results of the analysis of the design of a thermoelectric coolbox with a wind turbine, it has the potential and benefits for the fishing profession and can be realized into a product.